In This Corner: An Analysis of Federal Boxing Legislation - Ehrlichman, Brad (The Columbia Journal of Law & the Arts, 2019)
Muhammad Ali—arguably the greatest boxer of all time—lay beaten in a hospital bed. Defeated by his former sparring partner, Larry Holmes, Ali was battered and prone: King Arthur run through by Mordred. An aide to Don King, Ali’s long-time promoter, stole into the room with a briefcase. At the time, King owed Ali over $1 million. Inside the briefcase was $50,000 in cash, which Ali— defeated—accepted after signing a release dropping all claims against King. While the Senate’s version of what was to ultimately become the Muhammad Ali Boxing Reform Act (“Ali Act”), referenced only Ali’s “unsurpassed” “career achievements and personal contributions to the sport [of boxing],” it is likely that this shameful episode was present in legislators’ minds when honoring their bill’s revered—yet tragic—eponym. Passed in 2000, the Ali Act was Congress’s second foray into the arena of boxing legislation, following the Professional Boxers Safety Act (“PBSA”) of 1996.5 While the PBSA was aimed at protecting boxers within the ring, the Ali Act was intended “to protect the rights and welfare of professional boxers . . . by preventing certain exploitative, oppressive, and unethical business practices” outside the ring.6 Indeed, tales of corruption are as much a part of the folklore of boxing as legends of great fights, indomitable champions and intrepid underdogs. Thus, for every retelling of Marvin Hagler’s brutal three-round tilt with Thomas Hearns, there is an account of the indictment of former International Boxing Federation president Robert Lee for allegedly extorting $338,000 in payoffs to manipulate rankings.7 For every awed recollection of Joe Louis’s unprecedented twenty-five consecutive heavyweight title defenses, there is the story of former heavyweight champion Tim Witherspoon being forced to sign four contracts while being promoted by Don King: one made King his exclusive promoter; another made King’s son, Carl, Witherspoon’s manager, entitled to thirty-three percent of his earnings; the third was a duplicate of Carl King’s managerial contract, only this one entitled him to fifty percent of Witherspoon’s earnings; and the last was completely blank, allowing King to write in any terms he wished.8 And, for every narration of Buster Douglas’s knockout victory of the seemingly invincible Mike Tyson in Tokyo, there is the embarrassing anecdote about Darrin Morris—a supermiddleweight boxer who died in October of 2000, only to climb the World Boxing Organization (“WBO”) rankings until he was able to attain in death what eluded him in life: a top-five ranking.